P2X7 Receptors in Neurodegeneration: Potential Therapeutic Applications From Basic to Clinical Approaches - Territo, Paul R.; Zarrinmayeh, Hamideh (Frontiers in Cellular Neuroscience, 2021)
Purinergic receptors play important roles in central nervous system (CNS), where the bulk of these receptors are implicated in neuroinflammatory responses and regulation of cellular function of neurons, microglial and astrocytes. Within the P2X receptor family, P2X7 receptors is generally known for its inactivity in normal conditions and activation by moderately high concentrations (>100 μM) of extracellular adenosine 5′-triphosphate (ATP) released from injured cells as a result of brain injury or pathological conditions. Activation of P2X7R contributes to the activation and proliferation of microglia and directly contribute to neurodegeneration by provoking microglia-mediated neuronal death, glutamate-mediated excitotoxicity, and NLRP3 inflammasome activation that results in initiation, maturity and release of the pro-inflammatory cytokines and generation of reactive oxygen and nitrogen species. These components of the inflammatory response play important roles in many neural pathologies and neurodegeneration disorders. In CNS, expression of P2X7R on microglia, astrocytes, and oligodendrocytes are upregulated under neuroinflammatory conditions. Several in vivo studies have demonstrated beneficial effects of the P2X7 receptor antagonists in animal model systems of neurodegenerative diseases. A number of specific and selective P2X7 receptor antagonists have been developed, but only few of them have shown efficient brain permeability. Finding potent and selective P2X7 receptor inhibitors which are also CNS penetrable and display acceptable pharmacokinetics (PK) has presented challenges for both academic researchers and pharmaceutical companies. In this review, we discuss the role of P2X7 receptor function in neurodegenerative diseases, the pharmacological inhibition of the receptor, and PET radiopharmaceuticals which permit non-invasive monitoring of the P2X7 receptor contribution to neuroinflammation associated with neurodegeneration.